2013
DOI: 10.1080/0305215x.2012.678493
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of cold-formed steel portal frames taking into account the effect of building topology

Abstract: Cold-formed steel portal frames are a popular form of construction for low-rise commercial, light industrial and agricultural buildings with spans of up to 20 m. In this article, a real-coded genetic algorithm is described that is used to minimize the cost of the main frame of such buildings. The key decision variables considered in this proposed algorithm consist of both the spacing and pitch of the frame as continuous variables, as well as the discrete section sizes. A routine taking the structural analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…It has also been observed that using the real coded genetic algorithms, large population sizes are needed in order to obtain the optimum solution consistently [25].…”
Section: Optimisation Methodologymentioning
confidence: 99%
“…It has also been observed that using the real coded genetic algorithms, large population sizes are needed in order to obtain the optimum solution consistently [25].…”
Section: Optimisation Methodologymentioning
confidence: 99%
“…In order to consider discrete and continuous design variables, special crossover and mutation functions enforce variables to be integers [35]. It has been observed that using the real coded genetic algorithms, large population sizes are needed in order to obtain the optimum solution consistently [36]. To help improve computational efficiency and reliability, solution space reduction and enhanced exploration based on larger initial populations, respectively, are employed here as in [2].…”
Section: Optimisation Methodologymentioning
confidence: 99%
“…There are not many works on steel frames made of cold-formed sections. In one of the recent study real-coded genetic algorithm is utilized to develop optimum design algorithm for cold-formed steel portal frames which minimizes its cost [19]. The design variables consist of continuous and discrete variables.…”
Section: Introductionmentioning
confidence: 99%